Effect of Processing Parameters on Green gram Milling - Singh, Sanjay Kumar; Agrawal, U S (Journal of Agricultural Engineering, 2002)
The effect of processing parameters (moisture content, outlet opening, roller speed, roller length, and roller inclination) on hulling efficiency of green gram was studied using emery roller machine. Models were developed to represent the milling responses (coefficient of hulling, coefficient of wholeness of kernel and hulling efficiency) as functions of processing parameters and a common compromise point was found to obtain optimal values of milling responses. The results indicated that the hulling efficiency increased with increase in roller speed and roller length and decreased with increase in outlet opening and roller inclination. The effect of roller inclination was less prominent as compared to those of the other parameters. The range of moisture content 10-12 % (db); outlet opening 140 - 182 mmÂ²; roller speed 13 m/s; roller length 25 - 32 cm and roller inclination 5 degree were found to be the most suitable parameters for green gram milling.